Peran Green Accounting dalam Meningkatkan Kinerja Lingkungan Koperasi Simpan Pinjam: Sebuah Systematic Literature Review - Sarah Safira; Frita Dwi Sulistiani; Salsabilla Maharani; Desty Maharani; Annisa Puji Rianti; Irfan Saefuloh (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
Environmental sustainability has become a strategic issue in organizational governance. Organizations are expected not only to achieve economic objectives but also to demonstrate accountability for environmental preservation. Green accounting has emerged as an accounting approach that integrates environmental aspects into organizational recording, measurement, reporting, and decision-making processes. This study aims to analyze the role of green accounting in improving environmental performance in savings and loan cooperatives through a Systematic Literature Review (SLR) approach. The study adopted the PRISMA protocol to identify, screen, and evaluate relevant scientific publications. Literature was collected from Google Scholar, Scopus, Garuda, and Crossref databases covering the period 2020–2025. The review focuses on the relationship between green accounting implementation, stakeholder theory, and environmental performance. The findings indicate that green accounting contributes to environmental performance through environmental cost management, resource efficiency, transparency enhancement, and organizational accountability. The study also identifies management commitment, technological development, and environmental awareness as supporting factors, while limited human resources and environmental accounting knowledge remain significant barriers. The novelty of this study lies in proposing a conceptual framework that integrates stakeholder theory, green accounting, and environmental performance within the context of savings and loan cooperatives.